Traffic density based adaptive QoS classes mapping for integrated LTE-WiMAX 5G networks - Ali, Muntadher Alshaikh; Esmailpour, Amir; Nasser, Nidal (IEEE International Conference on Communications (2003), 2017)
The next generation of mobile broadband technologies, namely the Fifth Generation (5G), will include an integration of legacy technologies like the Long Term Evolution (LTE), the Worldwide Interoperability for Microwave Access (WìMaX), the Wireless Fidelity (Wi-Fi), etc. However, Quality of Service (QoS) details are not fully defined for the integrated networks, and the subject is left open to be explored by the vendors. Provisioning of QoS guarantees for a heterogeneous network is contingent upon the execution of an appropriate mapping among the QoS classes of the participating technologies. LTE and WiMAX are two flourishing technologies in the Fourth Generation (4G) and will remain so in 5G. Therefore, an adaptive QoS class mapping strategy is proposed for the incorporated LTE-WiMAX 5G Network. Simulation results revealed a satisfying performance in terms of QoS measures such as response time and Packet Loss Rate (PLR) for almost all types of traffic.